Environmental Health Needs Among Latinas in Cleaning Occupations: A Mixed Methods Approach - Erin Speiser; Genevieve Pinto Zipp; Deborah A. DeLuca; Ana Paula Cupertino; Evelyn Arana-Chicas; Elli Gourna Paleoudis; Traci N. Bethea; Benjamin Kligler; Francisco Cartujano-Barrera (SAGE Publishing, 2022)
In the U.S., approximately half of maids and housekeeping cleaners are Latino or Hispanic, while the vast majority are women (88.3%). This largely immigrant, underserved workforce faces complex factors, which may contribute to adverse health outcomes. To understand relevant barriers and challenges, this mixed-methods study explored the environmental health needs of a heterogeneous group of Latinas in New Jersey (NJ) who clean occupationally, and consisted of 3 focus groups (N = 15) with a cross-sectional survey (N = 9), both conducted in Spanish. Participants were recruited from community-based English as a Second Language classes in Hackensack, NJ. Analysis of focus group audio recordings included descriptive and in vivo coding followed by inductive coding to explore thematic analysis. The survey responses were evaluated using descriptive statistics. As per the survey results, the environmental health needs of this population include sore muscles, back problems, asthma, other respiratory issues, migraine or headache, and skin issues (rash, etc.). In the group discussions, the roles of genetics, food, and chemical exposures in cancer etiology were of great interest and a variety of opinions on the topic were explored. Both the focus group discussions and survey responses suggested that this population also faces barriers including lack of training, chemical exposures and inadequate personal protective equipment (PPE). These barriers are compounded by daily environmental exposures from personal home cleaning practices. The development of culturally- and linguistically-appropriate interventions are warranted to better protect the health of essential occupational cleaners who keep homes, businesses and schools clean.